Una visión optimista sobre el periodismo africanista español - Jurado Quintana, Ángeles (2015)
The media have a major social work and endeavors with a commodity of a very special nature, the information. But media are also businesses subject to the vagaries of the market and the law of supply and demand. In the Spanish case, media have traditionally shown a very superficial and sporadic interest in African realities, usually spurred by conflict, famine or natural disaster. It is common to hear or read among journalists who are dedicated to the continent that "Africa does not sell" and the complaints of those professionals are normal when trying to sell their stories and articles to mainstream media or even charge a decent remuneration for their knowledge, effort and commitment to report and / or from Africa. However, and despite this bleak portrait with which many journalists agree, it is also true that, from the point of view "Africanist" there is the perception of new times and there are reasons for optimism.